Pengaruh Ekstrak Sargassum sp. terhadap Aktifitas Fagositosis Ikan Kakap Putih (Lates calcarifer) yang diinfeksi Bakteri Vibrio alginolyticus - Monica Azuwarita; Rika Wulandari; Aminatul Zahra (Intek Akuakultur, 2021)
Sargassum sp. is a natural synthesis product it has bioactive metabolites as flavonoid which can increase the fish body's defense system from attacks of disease. The purpose of this study was to determine the effect of Sargassum sp. added into the feed against the phagocytic activity of white snapper infected by Vibrio alginolyticus bacteria. This research was conducted using a completely randomized design method with 4 treatments and 3 replications, with K treatments (Sargassum sp. extract 0 ppm), A (Sargassum sp. extract 50 ppm), B (Sargassum sp. extract 70 ppm), and C (Sargassum sp. extract 90 ppm). The results showed that the administration of Sargassum sp. extract in white snapper feed and after infected by Vibrio alginolyticus bacteria was able to giving effect on phagocytic activity. The best concentration was obtained in treatment B with Sargassum sp. extract. 70 ppm with the highest phagocytosis activity value of 77.33%, and the highest survival rate of 43.33%.